The impact of digital flashcards on cardiovascular physiology academic performance in a medical course – a dose-dependent effect between the amount of training and academic success. (25th November 2020) - Santos-Ferreira, D; Guimaraes, B; Tsisar, S; Goncalves-Teixeira, P; Ladeiras-Lopes, R; Fontes-Carvalho, R; Leite-Moreira, A
Abstract: Background: Digital flashcards are used to review factual knowledge through active-recall and spaced-repetition, while allowing subsequent self-assessment. Purpose: To assess if using digital flashcards is associated with cardiovascular physiology academic success and better knowledge retention in short- and medium-terms, through a dose-dependent effect. Methods: We conducted a single-faculty cohort study of 2nd-year medical students enrolling in cardiovascular physiology course, using a platform comprising 676 original flashcards. The grades from 0–20 scale of three exams were analyzed, being the latest optional and performed 1 month after the end of the course. One-sample t-test was used to compare the grades between flashcard users versus non-users, and the amount of training was correlated with the exams results using Pearson's correlation. Also, multiple linear regression models were created, using the respective grades as the dependent variable. A p value of <0.05 was considered statistically significant. Results: From 312 students enrolled, 279 agreed to participate in this study, and 87% used the platform. Flashcard-users exhibited higher grades versus non-users (11.83±3.57 vs. 9.50±3.55, p<0.001; 12.47±3.03 vs. 11.45±3.24, p=0.225; 10.24±4.66 vs. 7.51±4.46, p=0.041; 1st, 2nd and 3rd exams, respectively). Among flashcard-users, the amount of training was positively correlated with the academic success (r=0.366, r=0.350, r=0.286; 1st, 2nd and 3rd exams, respectively, p≤0.001 for all). Multiple linear regression models showed a statistically significant association between the theoretical exam results and the number of flashcards studied – for every 1000, there was an increase in 0.98 (p=0.001), 1.22 (p=0.017) and 1.00 (p=0.022) in the grades of the 1st, 2nd and 3rd exams, respectively. Conclusion: Studying cardiovascular physiology through digital flashcards has a moderate correlation with the exams results, exhibiting a positive and consistent dose-dependent effect, both in short- and medium-terms. Therefore, this strategy seems to improve academic success by increasing knowledge retention. Funding Acknowledgement: Type of funding source: None